2019
DOI: 10.1007/s10620-018-5452-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Demethylase Genes, FTO and ALKBH1, Is Associated with Prognosis of Gastric Cancer

Abstract: Background Reversible N 6 -methyladenosine (m 6 A) modifications in messenger RNAs can be categorized under the field of “RNA epigenetics.” However, the potential role of m 6 A-related genes in gastric cancer (GC) prognosis has not been systematically researched. Aims This study was aimed at providing insights into the prognostic role of m 6 A-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 31 publications
4
77
0
Order By: Relevance
“…First, we show that FTO expression in colon cancer cells is finely regulated at the post-transcriptional level, though the precise underlying mechanism remains to be determined. This observation is in agreement with a recent report in gastric tissue [38] and stresses the importance of quantifying gene expression at the protein level for diagnostic purpose. Second, as will be discussed below, FTO activity and substrate specificity may vary with its subcellular distribution.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First, we show that FTO expression in colon cancer cells is finely regulated at the post-transcriptional level, though the precise underlying mechanism remains to be determined. This observation is in agreement with a recent report in gastric tissue [38] and stresses the importance of quantifying gene expression at the protein level for diagnostic purpose. Second, as will be discussed below, FTO activity and substrate specificity may vary with its subcellular distribution.…”
Section: Discussionsupporting
confidence: 93%
“…Decreased expression is achieved post transcriptionally, since quantitative PCR (qPCR) analysis of FTO mRNA levels showed no significant differences between CTC lines and primary/metastatic patient derived lines ( Figure 3b ). A similar disconnect in FTO mRNA/protein was reported in gastric tumors [38].…”
Section: Resultssupporting
confidence: 78%
“…Therefore, YTHDF1 may be a marker of HCC. In GC, the abnormal expression of FTO has significant prognostic value; hence, FTO may play important roles in GC progression and metastasis [58]. Similarly to the report of Li, Xu et al [59] concluded that FTO expression might play an important role in promoting the occurrence of GC and might be an important molecular marker for the diagnosis and prognosis of this disease.…”
Section: Pancreatic Cancermentioning
confidence: 92%
“…1b). Interestingly, FTO has been reported to be highly expressed in ESCC and other malignant tumors such as melanoma and gastric cancer, implying its distinct role in EAC [28,40,41]. In the correlation analysis, KIAA1429 was found to present the strongest correlation with YTHDF3.…”
Section: Discussionmentioning
confidence: 93%